The influence of celebrity politician’s tiktok towards young voters’ voting behaviour - Gui, Shelby Chin Fung (2023)
TikTok is one of the well-established short-form contents apps that enables users to create various types of contents. However, users are not only access TikTok for entertaining, but also accessing political information on TikTok. During the 15th General Election (GE15), the voting age for Malaysia citizens has been lowered down from 21 to 18, thereby allowing the young generation to participate in the electoral process. In order to build relationship with young voters, politicians started to transform their marketing strategies to online media, including TikTok. Many politicians are utilizing TikTok to create contents in innovative ways to promote their political ideologies or show support to a particular political party, resulting in a new definition of “celebrity politicians”, which represents politicians who are actively on social media and have many followers. This study aimed to examine the effects of celebrity politicians on young voters’ voting behaviour, as well as to discover the advantages of celebrity politicians’ influence in politics. This study employed quantitative method to achieve the research objectives, using survey distribution to 100 respondents, with 42 male and 58 female respondents. The results indicates that most respondents believe that celebrity politicians have the ability to influence young voters’ voting behaviour and affect voters’ decision-making in election. The results also shows that celebrity politicians make politics topics that are more accessible. However, most respondents do not prefer to receive political information on TikTok. This study consists of few limitations and provides some recommendations for future study.